Indo-Pacific strategy and Europe – from politics through defence and economy to cultural and AI diplomacy. The example of the Czech Republic - Fostikov, Aleksandra (Napredak, 2025)
In the past decades, the increase in the importance of the Indo-Pacific region, which has become not only a new geopolitical and geoeconomic, but also a geotechnical centre, led to a series of activities both of individual countries and the European Union and its member-states, resulting in a set of strategies for the Indo-Pacific during the second decade of the 21st century. The same process continued in the current, third decade. Due to their significance, the enacted strategies soon became the subject of study, whereas lately the focus has been placed exactly on analyzing the activities of individual countries. On this occasion, we have dedicated attention to the research of the activities of the Czech Republic, which adopted its strategy in 2022, immediately after the adoption of the European Union’s Strategy for the Indo-Pacific (2021) and subsequently, this region also found its place in the official politics of this country, namely in the Foreign Policy Concept (2025), as well in the National Cybersecurity Strategy (2025).